Inequalities in diagnosis and registration of pediatric very rare tumors: a European study on pleuropulmonary blastoma - Grigoletto, V; Tagarelli, A; Sparber-Sauer, M; Koscielniak, E; Orbach, D; Duplan, M; Stachowicz-Stencel, T; Bien, E; López-Almaraz, R; Ben-Ami, T; Pourtsidis, A; Österlundh, G; et al. (European journal of pediatrics, 2020)
Very rare tumors (VRTs) account for up to 11% of childhood cancers. Dedicated national groups and registries only exist in some European countries. Pleuropulmonary blastoma (PPB) is a very rare intrathoracic pediatric tumor with a potentially severe prognosis. Due to its rarity, it sometimes goes unrecognized. We investigated PPB diagnostic capability and possible correlations between diagnostic performance and VRT-dedicated activities. The number of cases of PPB registered between 2000 and 2014 at pediatric oncology centers in Europe was compared with the number of expected cases. Data sources included VRT registries, population-based cancer registries, and hospital registries. Data were obtained for 25 countries, grouped into 4 geographical regions. The expected cases were 111, and the observed cases were 129. The observed-to-expected ratio was 1.86 for Northern Europe, 1.33 for Southern Europe, 1.22 for Central Europe, and 0.65 for Eastern Europe. More cases than expected were registered in all countries with an official VRT registry.Conclusion: The number of cases observed is consistent with expectations, but disparities exist across Europe. Difficulties in diagnosing PPB emerged in most Eastern countries. The incidence rate of PPB may be underestimated. The creation of VRT-dedicated groups and a European Registry for VRTs could help to reduce inequalities.What is Known:• Very rare pediatric tumors are often not recognized, despite representing almost 11% of childhood cancers .• Pleuropulmonary blastoma is a rare pediatric tumor with a poor prognosis.What is New:• The ability to diagnose and register pleuropulmonary blastoma varies in Europe.Registries dedicated to very rare pediatric tumors improve the diagnostic rates.• The incidence rate of pleuropulmonary blastoma may currently be underestimated.
Keywords: Lung Neoplasms; předškolní dítě; nádory plic; retrospektivní studie; Child; novorozenec; incidence; Humans; lidé; Retrospective Studies; registrace; mladiství; Pulmonary Blastoma; Female; Male; Infant, Newborn; Europe; kojenec; mužské pohlaví; Infant; ženské pohlaví; Cross-Sectional Studies; průřezové studie; Child, Preschool; Evropa; dítě; Registries; Incidence; Adolescent; plicní blastom